Highly Stereoselective Synthesis of Fluoroalkene Dipeptides via the Novel Chromium(II)-Mediated Carbon–Fluorine Bond Cleavage/New Carbon–Carbon Bond Formation - Nihei, Takashi; Nishi, Yuji; Ikeda, Natsumi; Yokotani, Saya; Ishihara, Takashi; Arimitsu, Satoru; Konno, Tsutomu (Synthesis, 2016)
An efficient chromium(II)-mediated reductive coupling reaction of various CBrF2-containing molecules and aldehydes has been developed. This reaction proceeds presumably via the monofluorinated dichromium(III) intermediate generated by the carbon–fluorine bond activation, and provides a general and straightforward access to synthesize a variety of (E)- or (Z)-β-fluoroallylic alcohols in a highly stereoselective manner. Based on the novel reductive coupling, four types of fluoroalkene dipeptide analogues could be stereoselectively prepared.
Keywords: β-fluoroallylic alcohol derivatives; carbon–fluorine bond activation; chromium(II) chloride; stereoselective; fluoroalkene bioisosteres